2011
DOI: 10.1080/15320383.2011.620044
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CEC and pH in Cd Retention from Soils of North of Iran

Abstract: Cadmium (Cd) is a critical environmental chemical in which sorption reactions control its entry into soil solution. The aim of the present study was to evaluate Cd sorption characteristics of some soils of the northern part of Iran with a wide range of physicochemical properties. Duplicates of each sample were equilibrated with solutions containing 5 to 500 mg Cd L -1 with 0.01 M CaCl 2 as background solution. The quantity of Cd retention was calculated as the difference between initial and equilibrated Cd con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Figure 5 and Table 4 A also indicate that soil CEC was positively correlated with soil available Cd. OM, as the main sorbent in soil [ 45 ], exhibited a significant positive correlation with CEC in this case ( r = 0.344 **, p < 0.01; Figure 5 ). The reason for the positive correlation between OM and available Cd may also explain why CEC was positively correlated with soil available Cd.…”
Section: Discussionmentioning
confidence: 81%
“…Figure 5 and Table 4 A also indicate that soil CEC was positively correlated with soil available Cd. OM, as the main sorbent in soil [ 45 ], exhibited a significant positive correlation with CEC in this case ( r = 0.344 **, p < 0.01; Figure 5 ). The reason for the positive correlation between OM and available Cd may also explain why CEC was positively correlated with soil available Cd.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of intercropping treatment also showed in cation exchange capacity, which reflected the soil fertility retention capacity, increasing by 5.16%–32.26% leading to the better growth of plants showing in the form of higher biomass. Frost and Griffin (1977) reported that high pH, high CEC of soils may have favoured the conditions for low Cd availability (Esfandbod et al, 2011), confirming that high CEC was conductive to reducing Cd effectiveness. Treatment in the middle of this experiment may cause changes in soil salinity, resulting in an increase in wheat biomass and a decrease in Cd content.…”
Section: Discussionmentioning
confidence: 95%